26. STEM CELLS - APPLICATIONS RELATED TO MALE & FEMALE REPRODUCTIVE ORGANS (Vietnam Journal of Community Medicine, 2026)
Humans are formed from the first stem cell (embryo) which then multiplies and differentiates into a complete human body consisting of 220 organs and about 37 to 40 trillion cells. Stem cells are cells that have the ability to reproduce and differentiate into cells of organs in the body. By means of a comprehensive literature review, it is shown that: Using induced pluripotent stem cell (iPSC) therapy, mesenchymal stem cells (MSC) have been proven effective in treating female infertility, prolonging youth. hiPS (Human Induced Pluripotent Stem) stem cell lines are used to treat patients with Kline-feder syndrome and azoospermia with Y chromosome azoospermia. Research directions for restoring fertility with stem cells include: (1) Expanding spermatogonial stem cells (SSC) in vitro and then autotransplanting testes; (2) Automated whole testicular biopsy transfer; (3) In vitro spermatogenesis.
Keywords: Stem cell, reproductive organs, application